Photovoltage spectroscopy of direct and indirect bandgaps of strained Ge1-xSnx thin films on a Ge/Si(001) substrate. (1st June 2019) - Kondratenko, S.V.; Hyrka, Yu.V.; Mazur, Yu.I.; Kuchuk, A.V.; Dou, W.; Tran, H.; Margetis, J.; Tolle, J.; Yu, S.-Q.; Salamo, G.J.
Abstract: The near-bandgap optical properties of Ge1- x Sn x alloys were characterized by photovoltage spectroscopy and spectral ellipsometry measurements. Contributions of Urbach tailing as well as direct and indirect optical transitions were observed. The compositional dependence of direct bandgaps of strained GeSn films grown on a Ge buffered Si substrate was studied for up to 15% Sn content. The contribution to the photovoltage spectra of Ge1- x Sn x alloys ( x < 6%) from indirect optical transitions was observed at lower energies than from direct bandgaps. Using bowing parameters of b GeSn Γ = 3.16–0.5 x and b GeSn L = 1.93 eV, a correlation was detected between calculated and measured indirect and direct bandgaps at 82 K. As the Sn content was increased, the difference between the energies of the indirect and direct bandgaps decreased, resulting in a smaller contribution of the indirect transitions due to competition with direct transitions and Urbach tails. Two sublayers with different Sn content, strain values and bandgaps were observed for samples with x ∼12%. The results indicated that strain relaxation in films with thicknesses exceeding a critical value occurs via formation of a Sn-rich top layer with higher direct bandgap. These findings have important implications when designing IR photodetectors or solar cells. Graphical abstract: Image 1